2021
DOI: 10.1155/2021/9809990
|View full text |Cite|
|
Sign up to set email alerts
|

LDH and GGT/ALT Ratio as Novel Prognostic Biomarkers in Hepatocellular Carcinoma Patients after Liver Transplantation

Abstract: Background. Liver inflammation indices reflect its inflammatory microenvironment, which may play a role in the proliferation, invasion, and migration of carcinoma. This study is aimed at exploring the prognostic significance of serum lactate dehydrogenase (LDH) levels and gamma-glutamyl transferase (GGT)/alanine aminotransferase (ALT) ratio in hepatocellular carcinoma after liver transplant (LT). Methods. We retrospectively analyzed data from 155 patients with a pathologically confirmed diagnosis of hepatocell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…There is increasing evidence that poor prognosis and poor treatment response are associated with elevated LDH levels [34]. Zhang et al also found a negative correlation between the OS and LDH levels [35].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that poor prognosis and poor treatment response are associated with elevated LDH levels [34]. Zhang et al also found a negative correlation between the OS and LDH levels [35].…”
Section: Discussionmentioning
confidence: 99%
“…Serum GGT combined with the AST/ALT and GGT/ALT ratios have been shown to be of great value in predicting the prognosis of HCC ( 34 , 36 , 37 ). However, the utility of the GGT/AST for diagnosing AFP-negative HCC patients has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Our nomogram model showed a high performance in the diagnosis of AFP-negative HCC in both training (AUC=0.838) and validation (AUC=0.840) sets. Few previous studies have focused on the construction of a nomogram model based on serological indicators for the diagnosis of AFP-negative HCC, with most limited to the analysis of single- or several-factor ROC diagnostic curves showing incomplete consideration of factors and a single study sample of diseases that may bias the results( 30 , 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…High blood levels of DCP have been associated with an increased risk of HCC recurrence in patients with HCC undergoing LT. [30][31][32][33] In addition, high blood DCP levels were associated with mortality in patients with HCC undergoing LT in a study of 213 patients [34] and in another study of 246 patients. [35] Lactate dehydrogenase A study of 155 HCC patients undergoing LT [36] has found an association between high blood lactate dehydrogenase (LDH) and mortality.…”
Section: De-gamma-carboxy-prothrombinmentioning
confidence: 99%